PENGGUNAAN KARYA CIPTA @AKUBAYIGULA PADA THREAD TWITTER OLEH YOUTUBER NESSIE JUDGE: Use Of @Akubayigula’s Copyrighted Work On Twitter Thread By Youtuber Nessie Judge - Laura Marthilda Rawentinah Kigogo; Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2024)
Social media content is often used by others by not appreciating the effort, which have the potential of copyright infringement such as the recent case which @akubayigula's copyright work was used by Nessie Judge without permission so the thread’s owner being objection. The problem in this research is how the legal protection of @akubayigula's twitter thread based on Copyright Law and whether the use of @akubayigula's twitter thread by Youtuber Nessie Judge is copyright infringement. This research is normative legal research, descriptive in nature, using primary and secondary data, data collection using literature study and interviews, drawing conclusions using the deductive method.The result of this research based on article 40 of law of the Republic Indonesia number 28 of 2014 on copyright, thread @akubayigula is copyrighted work. The conclution is Nessie Judge's actions is a copyright infringement specifically included in the copyright infringement form of announcement, distribution, and communication of creation.